The Impact of Environmental Taxes on Greenhouse Gas Emissions in Selected BRICS Countries - Hlongwane, Nyiko Worship (International Journal of Economics and Financial Issues, 2025)
The study investigates the impact of environmental taxes on greenhouse gas emissions in selected BRICS nations. While existing literature investigates the impact of environmental taxes on greenhouse gas emissions, there is a gap in studies that focus on BRICS nations. This study utilized panel data from reputable secondary sources such as the World Bank, Global Economy, and OECD from 1995 to 2022. The study employed the PARDL model and found that in the short run, environmental taxes effectively reduce greenhouse gas emissions in Brazil and China, whereas for South Africa they are ineffective. The robust results of the FMOLS and DOLS models discovered that environmental taxes are associated with increasing greenhouse gas emissions both in the short and long-run periods. Based on empirical evidence, the study recommends a disaggregated approach to the implementation of environmental taxes to effectively address the issue of rising greenhouse gas emissions and climate change mitigation.